Readmissions and deaths from complications associated with alcohol abuse - Cleiton José Santana; Magda Lucia Felix de Oliveira; Mirella Machado Ortiz Modesto; Marcia Regina Jupi Guedes; Paola Kallyanna Guarneri Carvalho de Lima; Giovana Alves Santos (Universidade Federal do Ceará, 2022)
Objective: to analyze readmissions and deaths of hospitalized patients due to the effects of alcohol abuse. Methods: documentary, longitudinal and retrospective study, by analysis of hospital records, carried out in a teaching hospital, by descriptive analysis, univariate association, using Pearson's chi-square test. Results: 399 readmissions of 278 patients were analyzed. Two hospitalizations predominated (69.6%). Most were male (85.2%), and the mean age was 47.15 years (± 13.91); 91.2% were readmissions due to the use of alcoholic beverages, with 45.3% of complications associated with injuries, poisoning and external causes of morbidity and mortality. Twenty-seven (9.7%) patients died. The readmissions of retirees/housewives had an odds ratio of 3.0 of progressing to death. Conclusion: the analysis showed prevalent readmissions and mortality in males, productive age group, with a significant association of risk in intensive care patients and cause of death associated with complications of chronic alcohol use. Contributions to practice: the identification of the causes of readmissions helps nursing professionals in the early recognition of signs of severity and serves as a subsidy for the development of prevention strategies and actions to improve the care network.